Máquina do tempo: ressonância de H. G. Wells na ficção distópica do século XX - Lira, Thaíse Gomes (2019)
The time machine (2018 [1895]), H. G. Wells’s first novel, is one of the books which represent the British dystopian impulse and that influenced the dystopian narratives of the twentieth century, so that its reflection is still perceived in the works of the 21st century. Dystopia, whose nomenclature is recent in literary studies, lacks further investigation in Portuguese, and I direct this study towards that sense. The essence of the dystopic universe, in the form that it reached the last two centuries, goes back to a set of nineteenth-century works and also to the utopian narratives that emerged in the sixteenth century, from Thomas More's Utopia. Socialist and visionary, Wells established, in his first novel, consistent dialogues that would reverberate in Science Fiction and in the twentieth century dystopias, according to aspects pointed out by Figueiredo (2009) and other scholars. The central aim of this research is to analyze Wells's first novel, in the light of dystopian fiction, as one of the essential narratives of the British dystopian impulse of the nineteenth century that helped establish the structural basis of contemporary dystopia; in addition, it sought to: delimit the similarities and differences between Science fiction and dystopian fiction; to compare the utopian, the (post) apocalyptic and the dystopian Literature; to investigate the unusual, social, and spontaneously dystopian aspects of Wells's narrative that influenced the canonical works of the genre in the twentieth century. The research is supported by the studies of Frost (2013), Tomachevski (2013), Oliveira (1999), Todorov (2013; 2014), Culler (1999), Castro (2007) Soares (2007), Saer (2012) García (2007), Jameson (2005; 1982), Cardoso (2003), Cardoso (2006), Bozzetto (2007), Vieira (2010), Silva (2013), Miranda (2016), Booker (1994), Figueiredo (2009), Moraes (2012), Pavlovski (2012), Baccolinni (1995), Moylan (2016), Perrone-Moisés (2016), Arendt (1979) Aristóteles (2007), Genette (2017), among others. The analysis of the work allowed the observation that The Time Machine (2018 [1895]) is, in fact, a hybrid work, that mixes utopian, post-apocalyptic and dystopic traits; not all of the aspects pointed out by Figueiredo (2009) are identified in the work, but through his book, Wells also laid foundations for contemporary dystopias: high technology and the republican and socialist view, with Marxist critiques of social classes.